2007
DOI: 10.4321/s0004-06142007000600006
|View full text |Cite
|
Sign up to set email alerts
|

Hallazgos urodinámicos en mayores de 65 años: experiencia en el departamento 19 de la Agencia Valenciana de Salud (AVS)

Abstract: Resumen.-OBJETIVO: En este trabajo se pretende analizar los estudios urodinámicos realizados en mayores de 65 años en el Departamento 19 de la Agencia Valenciana de Salud (AVS) a fin de revisar nuestra actividad en ese segmento poblacional adscrito, durante el periodo de enero del 2001 y septiembre del 2006 y realizar una correlación clínico-urodinámica que ayude a alcanzar un diagnóstico evitando la necesidad de repetición de pruebas urodinámicas. MÉTODOS: Para ello, se ha realizado un estudio descriptivo tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
1
0
0
Order By: Relevance
“…Giner-Santamaría has observed that UDS confirms SUI in 60% of cases, it is not reproducible in 20%, and MUI is seen in 10%. On the other hand, in patients with UUI, UDS confirmed the diagnosis in 64% (bladder hyperactivity, urgency, or UUI); it was not reproducible in 12% and showed uncoordinated urination in 8% [37]. This diagnostic assessment was similar to that observed in our study, to diagnose UUI (64.7%), but not to confirm SUI (35.1%).…”
Section: Discussionsupporting
confidence: 86%
“…Giner-Santamaría has observed that UDS confirms SUI in 60% of cases, it is not reproducible in 20%, and MUI is seen in 10%. On the other hand, in patients with UUI, UDS confirmed the diagnosis in 64% (bladder hyperactivity, urgency, or UUI); it was not reproducible in 12% and showed uncoordinated urination in 8% [37]. This diagnostic assessment was similar to that observed in our study, to diagnose UUI (64.7%), but not to confirm SUI (35.1%).…”
Section: Discussionsupporting
confidence: 86%